Analisis Kebijakan Pengelolaan dan Budidaya Ekosistem Gambut di Indonesia: Penerapan Pendekatan Advocacy Coalition Framework - Bergas Chahyo Baskoro; Cecep Kusmana; Hariadi Kartodihardjo (Institut Teknologi Sepuluh Nopember, 2018)
Indonesia has a peat area of around 14.91 million hectares and has become the fourth largest owner of peat reserves in the world after Canada, Russia and the United States. Peatlands play a major role as carbon sinks and maintain a hydrological system. The destructive and oxidized characteristics of peat make the International and Indonesian Governments pay high attention to the management and protection of peat ecosystems. Through the Advocacy Coalition Framework (ACF) approach, this study found that there are a variety of actors and stakeholders who influence the dynamics of peat management and cultivation policy formulation in Indonesia. The actors and stakeholders formed a coalition by carrying out the logic of their respective belief systems, namely: Coalition A which has a belief system that peat land is a potential resource developed for cultivation and Coalition B which has a belief system that views peat ecosystems as vulnerable ecosystems that must be protected and rehabilitated. The results of this study are expected to be able to provide recommendations needed in realizing sustainable management of peat ecosystems.